Notary Authority to Provide Legal Counseling Service Based On Notary Law and Notary Code in Banjarnegara - Bondan Zakaria Bushido; Risky Eko Novi Artanto; Gunarto Gunarto (Jurnal Akta, 2019)
The purpose of this study was to determine and analyze Notary authority in Providing Legal counseling in terms of Act No. 2 of 2014 on Amendment of Act No. 30 of 2004 concerning Notary and Notary Code. And to analyze Obstacles and Solutions for a Notary in Role Gives Legal counseling.This study uses empirical juridical approach, the specification is descriptive analytical research, data sources used in the form of primary data obtained through interviews, secondary data with the literature study, qualitative analysis. The problem is analyzed using the theory of Authority and Accountability.Based on the results of this study concluded that 1) Notary authority in providing Legal counseling to Its clients can be divided into two (2) Criteria, namely a) Legal counseling followed by Creation Deed and b) Legal counseling without being followed by Creation Deed. 2) The obstacles in conducting Legal counseling, namely a) Effect of Kinship properties, b) Effect of Position, c) Influence of Consumerism, d) Profession into Business Activity, e) Due to Weak Faith. Solutions to resolve impediments in doing Notaries Legal counseling Legal counseling is doing that is not followed by Creation Deed.Keywords: Notary authority; Legal counseling.